(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2008)
In the exhaust dyeing of knit woven, jute/cotton fabrics a progressive addition process is developed and found most effective method in respect of cost and quality. It was done by an electronic device. In this paper we have developed it mechanically .It thought that it may be suitable for Bangladesh export oriented knit woven and blended fabrics dyeing units for its very low price. Bangladesh J. Sci. Ind. Res. 42(3), 357-360, 2007